Aloe vera gel as a natural solution for sustainable plant disease management and postharvest longevity in fruit crops amidst climate shifts - Lakshmi, S; Dheebakaran, G; Kokilavani, S; Senthil, A; Kavitha, C (Plant Science Today, 2025)
Climate variability and increasing postharvest losses have intensified the need for sustainable alternatives to synthetic pesticides and preservatives in horticultural systems. Conventional postharvest management approaches, while effective to some extent, face critical limitations; chemical treatments raise concerns over residues and human health, while many bio-based coatings such as starch, gum arabic and essential oils suffer from weak barrier properties, rapid degradation or inconsistent antimicrobial performance. This review evaluates the potential of Aloe vera gel extract as a natural, eco-friendly solution for plant disease management and postharvest quality preservation in fruits and vegetables, particularly under the pressures of climate-induced stresses. Rich in bioactive compounds such as acemannan, anthraquinones, flavonoids and saponins, A. vera gel demonstrates strong antimicrobial, antioxidant and immunomodulatory activities. Unlike other coatings, it not only forms an effective edible film but also contributes functional prebiotic and therapeutic benefits, making it uniquely multifunctional. It acts both as a biocontrol agent and a protective edible coating, delaying spoilage by inhibiting fungal and bacterial pathogens, reducing respiration rates and preserving textural and nutritional quality. Moreover, the integration of A. vera gel into composite coatings with biopolymers such as chitosan and alginate significantly enhances barrier properties and antimicrobial efficacy. Its dual role in both prevention and treatment of postharvest diseases, relevance in climate-resilient agriculture and compatibility with biodegradable packaging systems highlight its potential as a sustainable solution. Emphasis is also placed on its safety, affordability and role in promoting circular agro-economies, which are farming systems that minimize waste by reusing agricultural by-products and promoting resource efficiency. Future prospects lie in the standardization of formulations, elucidation of underlying mechanisms and field-level validation to facilitate its widespread adoption in postharvest management.